2017
DOI: 10.14735/amko2017426
|View full text |Cite
|
Sign up to set email alerts
|

Milk Thistle (Silybum Marianum) as a Supportive Phytotherapeutic Agent in Oncology

Abstract: Východiska:Ostropestřec mariánský (Silybum marianum) je rostlina, jejíž použití v medicíně má dlouholetou tradici, zejména v léčbě jaterních nemocí, kde se používá v rámci medicíny založené na důkazech (evidence-based medicine -EBM) i dnes. Její hlavní účinnou složkou je komplex flavonolignanů, známý jako silymarin. Silymarin se klinicky používá jako hepatoprotektivum, ale jeho potenciální účinky v léčbě onkologických onemocnění se v současné době dostávají do centra pozornosti. Cíl: Cílem této přehledové prác… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Our study showed that there is a significant decrease in % EF at baseline and after six months in the control group and these results in agreement with Ghaderian et al 2017 [11]; who found that there was a decline in % EF from 68±7.14 at baseline to 65.6 ± 9.3 after 6 months of doxorubicin administration in Childhood Acute Lymphoblastic Leukemia.…”
Section: Comparison Between Studied Groups At Baseline and After Chemsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study showed that there is a significant decrease in % EF at baseline and after six months in the control group and these results in agreement with Ghaderian et al 2017 [11]; who found that there was a decline in % EF from 68±7.14 at baseline to 65.6 ± 9.3 after 6 months of doxorubicin administration in Childhood Acute Lymphoblastic Leukemia.…”
Section: Comparison Between Studied Groups At Baseline and After Chemsupporting
confidence: 93%
“…The advantages of biomarkers include being minimally invasive, less expensive than echocardiography or nuclear techniques, and can easily be repeated without irradiation of the patient. Moreover, the interpretation of the results does not depend on the expertise of the operator, thus avoiding the possibility of interobserver variability [5] The prevention of anthracycline-induced cardiotoxicity is an important challenge in cancer survivorship. In trying to prevent or attenuate the side effects of doxorubicin administration, several strategies have been followed as dosage optimization, synthesis, and use of analogs or combined therapy like antioxidants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some Indian natural products have promise in relieving chemotherapy-induced hepatotoxicity (Metri et al, 2013 ). Recently, clinical trials show that milk thistle (main hepatoprotective ingredient silymarin) can effectively reduce hepatotoxicity in oncology patients (Frassova and Ruda-Kucerova, 2017 ). A edible mushroom mycelium product containing active hexose-correlated compound, can reduce hematotoxicity and hepatotoxicity, and improve the quality of life in patients with advanced cancer during chemotherapy (Ito et al, 2014 ).…”
Section: Prevention or Induction Of Hepatotoxicitymentioning
confidence: 99%
“…Due to its strong antioxidant and tissue regenerative properties, silymarin is being studied as a hepatic, neural, renal, and cardiac protective ingredient. [12]. Silymarin could be helpful in patients with oncology, particularly, for reducing the side effects of cancer chemotherapy [10].…”
Section: Introductionmentioning
confidence: 99%